Composing place : digital rhetorics for a mobile world - Greene, Jacob (Jacob Wes) (Utah State University Press, 2023)
"Composing Place proposes an innovative approach to engaging with the compositional affordances of mobile technologies. Jacob Greene utilizes a rhetorical framework through which writers can leverage the affordances of new technologies and develops this framework by drawing on theoretical approaches within rhetorical studies, multimodal composition, and spatial theory" --